Modified Bentall’s Procedure for Aortic Root Aneurysm : A Case Report (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: The modified Bentall(M Bentall) procedure is considered as the gold standard for patients requiring aortic root replacement, where the native aortic valve is required to be replaced.Case Presentation: We hereby present a case report of a patient who was diagnosed having moderate to severe Aortic Regurgitation (AR) with aortic root aneurysm. He was treated successfully by us with the M.Bentall procedure.Conclusion: As the aortic disease detection and surgical expertise improved in our country, a M.Bentall procedure is a suitable and safe treatment option for Aortic root aneurysm.JCMCTA 2021 ; 32 (2) : 147-150